HUBUNGAN RESPON IMUN DAN STRES DENGAN TINGKAT KEKAMBUHAN DEMAM TIFOID PADA MASYARAKAT DI WILAYAH PUSKESMASCOLOMADU KARANGANYAR - Mayasari, Dina; Pratiwi, Arum (Universitas Muhammadiyah Surakarta, 2009)
Typhoid fever still become the problem of society health in Indonesia with the incident between 350-180 case of per 100.000 resident and CFR gyrate 3%. This disease is pertained by a contagion which can groan the many people. Typhoid fever represent the acute infection disease is which is because of germ of Salmonella Typhi. Patient of typhoid Fever later can become the carrier and relapsing/relaps can be the happened. Factors causing the typhoid fever of recurrence for example : (1) immunity circumstance/endurance body of somebody, (2) personal hygiene which less be environmental though good generally, (3) consumption of food and beverage which risk (not yet cook/braise, lighted upon by the fly, not paid attention to its hygiene), (4) life style, (5) stress, etcetera. The main purpose of this research is to find out the the relationship of immune respon and stress with the relapse level of tifoid fever at the society in region of Puskesmas Colomadu Karanganyar. The research method of this research is use the descriptive desain research of corelatif with the device of cross sectional.Population of this research are all tifoid patients who are came on Puskesmas Colomadu in 2008, that are 130 patients. The technicall sampling of this research is purposive sampling with 43 patients. The technicall data collecting to be used on this research is by quesioner and interview to the patients, this quesioner include the immune respon, stress and relapse level of tifoid. The best conclude on this research hypothesis test conducted by a data analysis with the analysis bivariate crosstabulation hence result of value Chi-Square ( X²) to The Chi Square (X²) value for the relationship of immune respon and relapse level of tifoid is 31,279. With the sifnificant level 0,013 that is more smaller than 0,05 so on this case the Ho is rejected and Ha accepted, so its concluded that there is have a good relationship between immune respon and relapse level of tifoid. The Chi Square (X²) value for stress and relapse level of tifoid is 22,598 with significant level 0,021 smaller than 0,05, so Ho is rejected and Ha is accepted. This research is its found that there is have a good relationship of immune respon and stress with the relapse level of tifoid fever at the society in region of Puskesmas Colomadu Karanganyar